2002
DOI: 10.1021/ci025511e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Structural Connectivity Spectra Analysis (CoSCoSA) Models of Steroid Binding to the Corticosteroid Binding Globulin

Abstract: A three-dimensional quantitative spectrometric data-activity relationship (3D-QSDAR) model was developed that is built by combining NMR spectral information with structural information in a 3D-connectivity matrix. The 3D-connectivity matrix is built by displaying all possible carbon-to-carbon connections with their assigned carbon NMR chemical shifts and distances between the carbons. Selected 2D (13)C-(13)C COrrelation SpectroscopY (COSY) (through-bond nearest neighbors) and selected theoretical 2D (13)C-(13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
183
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(183 citation statements)
references
References 38 publications
0
183
0
Order By: Relevance
“…Finally, it should be emphasized that the 13 C NMR data employed here were unassigned, i.e., no supplementary structural information was used. It has been shown previously that it is possible to achieve improved performance by adding assigned structural information to the one-dimensional CoSA-type QSAR model …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it should be emphasized that the 13 C NMR data employed here were unassigned, i.e., no supplementary structural information was used. It has been shown previously that it is possible to achieve improved performance by adding assigned structural information to the one-dimensional CoSA-type QSAR model …”
Section: Discussionmentioning
confidence: 99%
“…Spectroscopic QSAR Methods. A set of QSAR methods have recently been put forward in which vibration frequencies (EVA, eigenvalue, i.e., vibrational normal mode in this context), MO energies (EEVA, electronic eigenvalue), and NMR chemical shifts (CoSA, comparative spectra analysis and its modifications ) are used to derive QSAR descriptors. It has been shown that spectroscopic methods can provide robust, predictive QSAR models for a large number of biological data sets.…”
Section: Introductionmentioning
confidence: 99%
“…The indirect approach confers advantages in simplicity of implementation and objectivity of model building. In most but not all cases, it has also shown improved accuracy and estimation performance compared with SAR and QSAR [21,22,23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, the SDAR methodology has been employed only in the development of models based upon the 13 C-NMR chemical shifts [20]. That implementation works well for carbon-rich organic chemicals [22,23,24], although it may be insufficient for adequate description of nitrogenated compounds. Lipophilic bases with a basic nitrogen atom are the major substrates of CYP2D6; the substrate nitrogen atom binds to aspartic acid on CYP2D, and substrate oxidation takes place at a distance of 5–7 Å from the nitrogen atom [25].…”
Section: Introductionmentioning
confidence: 99%
“…Beger and co-workers demonstrated that 13 C-NMR data can be used to produce reliable quantitative spectrometric data-activity relationship (QSDAR) models of binding to the corticosterone binding globulin, aromatase enzyme, and aryl hydrocarbon receptor [14][15][16][17]. Comparative structural connectivity spectra analysis (CoSCoSA) models of steroids binding to the corticosteroid were also presented [18]. The success of spectroscopic methods in SAR can be explained recalling that all spectroscopic quantities reflect certain intrinsic physicochemical properties of molecules that are related to their 3D structure.…”
Section: Introductionmentioning
confidence: 99%